Heat transfer for gas turbine internal cooling - Ng, Chean Yuan (2018)
High turbine inlet temperature is required for an efficient gas turbine engine. To maximise the turbine temperature, the internal channel of a turbine blade consists of rib-turbulators to enhance the heat transfer of the cooling air. This report focus on the effect of various rib configurations on cooling performance of internal channel of a turbine blade. High thermal hydraulic performance (THP) for a ribbed channel is desired to have good cooling performance. There are 6 types of different rib configurations in this study, that are square-extruded rib, cylinder-extruded rib, V-extruded rib, W-extruded rib, Jigsaw-extruded rib and 60˚-extruded rib. The averaged friction factor and Nusselt number in fully-developed region was determined at Reynolds number of 30,000 to calculate THP. Square-extruded rib and cylinder-extruded rib were further modified to have different base height and rib height to investigate its effect on THP. Uniform heat flux of 950W/m2 was supplied on both the bottom and upper ribbed walls. K-omega SST turbulence model in CFD Fluent was utilised to simulate the flow inside the internal channel. Results shows that square-extruded rib increases the THP value by 1.838% compared to the baseline channel. Besides that, an averaged Nusselt number between ribs in the fully-developed region for square-extruded and cylinder-extruded rib is also higher. Although increasing base height or extruded height raises averaged Nu values, their THP value drops by 7% due to the simultaneous increase in friction factor. Lastly, the V-extruded and W-extruded ribs have highest averaged Nu values among test channels yet their THP values are the lowest of values around 0.61 among test channel which makes them poor cooling channel design.